1980
DOI: 10.1080/14640748008401847
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism and Lexical Representation

Abstract: Forty-eight Hindi-English bilinguals completed two blocks of trials where each trial involved presentation of a letter string requiring a lexical decision. In the first block subjects were exposed to 22 words and 11 non-words in either English or Hindi. In the second block the original words were repeated in either the same language or in the alternative language. In this block the old (repeated) words were mixed with 22 new words, and 22 non-words. Twelve subjects were included in each of the four groups give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
2

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 17 publications
7
52
2
Order By: Relevance
“…The semantic priming effect is consistent with the findings reported previously by Kirsner et al (1984, Experiments 4 and 5) and Schwanenflugel and Rey (1986). The translation priming effect differed from previous results (see, e.g., Kirsner et al, 1980;Kirsner et al, 1984, Experiments 1 and 3;Scarborough et al, 1984), presumably because of the difference in time lag between the presentations of the prime comparisons were conducted using the protected r-test procedure (Fisher's least significant difference).…”
Section: '"supporting
confidence: 70%
See 2 more Smart Citations
“…The semantic priming effect is consistent with the findings reported previously by Kirsner et al (1984, Experiments 4 and 5) and Schwanenflugel and Rey (1986). The translation priming effect differed from previous results (see, e.g., Kirsner et al, 1980;Kirsner et al, 1984, Experiments 1 and 3;Scarborough et al, 1984), presumably because of the difference in time lag between the presentations of the prime comparisons were conducted using the protected r-test procedure (Fisher's least significant difference).…”
Section: '"supporting
confidence: 70%
“…The idea was that if translation equivalents are represented in languagespecific forms, then the repetition and translation conditions should result in different patterns of results. The general results showed that the processing of a concept could be affected by how the concept was presented or activated: Words repeated in the same language (i.e., the repetition condition), but not those repeated in the different language (i.e., the translation condition), resulted in shorter lexical decision times than did unrepeated new words (see, e.g., Kirsner, Brown, Abrol, Chadha, & Sharma, 1980;Scarborough, Gerard, & Cortese, 1984, for similar fmdings). In other words, lexical recognition could be generally facilitated by a represented identical item, but not by a functionally equivalent translation item.…”
Section: Hsuan-chih Chen and Man-la! Ng The Chinese University Of Honmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, in studies that have looked at whether a word in one language activates its translation in another language, influences of one language on the processing of the other have not been obtained, provided that the experiment has not been set up to encourage such translation (Kirsner, Brown, Abrol, Chadha, & Sharma, 1980;Kirsner, Smith, Lockhart, King, & Jain, 1984;Scarborough, Gerard, & Cortese, 1984;Watkins & Peynircioglu, 1983; see also Beauvillain & Grainger, 1987). The lexical decision task of Experiment 2 is not one that requires translation from one language into another; that is, it does not test whether the printed words SIT and CHAIR are translated into their corresponding ASL signs.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas repetition priming is reduced or even eliminated by a change in mode (Durso & Johnson, 1979), modality (Kirsner, Milech, & Standen, 1983;Kirsner & Smith, 1974;Morton, 1979) or language (Kirsner, Brown, Abrol, Chaddha, & Sharma, 1980) of the study andtestpresentations, semantic priming appears to beinsensitive to changes in each of these variables (Kirsner, Smith, Lockhart, King, & Jain, 1984;Meyer & Ruddy, 1974;Swinney, Onifer, Prather, & Hirshkowitz, 1979;Vanderwart, 1984).…”
mentioning
confidence: 99%